Reinventing Ishinomaki, Reinventing Japan? Creative Networks, Alternative Lifestyles and the Search for Quality of Life in Post-growth Japan. Issue 1 (2nd January 2016) - Klien, Susanne
ABSTRACT: This article aims to give an outline of recent developments in Ishinomaki, one of the cities worst affected by the Great East Japan Earthquake in March 2011. Before the disaster, the harbor town faced depopulation, aging residents, and a lack of prospects for the young, like many other stagnant regional cities. Since March 2011, Ishinomaki has seen an influx of short-, mid-, and long-term volunteers and young ambitious individuals who have moved from urban areas to initiate their own revitalization or social business projects. Drawing on and showing the limitations of Richard Florida's notion of the 'Creative Class', this paper approaches Ishinomaki's recent reinvention and transition from production to postindustrial multi-functionality as a phenomenon that can be seen as both a renaissance movement as well as the result of the structural instability of the labor market caused by Japan's transition into a mature postindustrial economy.